2017
DOI: 10.1088/1742-5468/aa53f6
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard transitions in the Kuramoto model: a role of asymmetry in natural frequency distributions

Abstract: Abstract. We study transitions in the Kuramoto model by shedding light on asymmetry in the natural frequency distribution, which has been assumed to be symmetric in many previous studies. The asymmetry brings two nonstandard bifurcation diagrams, with the aid of bimodality. The first diagram consists of stationary states, and has the standard continuous synchronization transition and a subsequent discontinuous transition as the coupling strength increases. Such a bifurcation diagram has been also reported in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Positive and negative ω 0 may exert different impacts on the model dynamics due to the asymmetrical bimodal frequency distribution. Incoherent states change stability with changing parameters at hopf bifurcation or pitchfork bifurcation [25,26,29,31,35]. We can get the bifurcation curves in Fig 5 from Eq (15), in which the more general conditions are considered analytically.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Positive and negative ω 0 may exert different impacts on the model dynamics due to the asymmetrical bimodal frequency distribution. Incoherent states change stability with changing parameters at hopf bifurcation or pitchfork bifurcation [25,26,29,31,35]. We can get the bifurcation curves in Fig 5 from Eq (15), in which the more general conditions are considered analytically.…”
Section: Plos Onementioning
confidence: 99%
“…Above K c , the incoherent state yields to a stationary partial synchronous state. For asymmetrical unimodal g(ω), the partial synchronous states are always time-dependent [26]. When g(ω) becomes a bimodal one, increasing coupling strength always first leads to a standing wave state, in which two synchronous clusters of oscillators oscillate at opposite mean frequencies and, then, to traveling wave states, in which synchronous oscillators rotate at the same frequency [27].…”
Section: Introductionmentioning
confidence: 99%
“…When exists, the synchronized uniformly twisted stationary state is represented as u syn st (x) = a(q)e iqx , with a(q) given by Eqs. (54) and (55).…”
Section: Synchronized Twisted Statementioning
confidence: 99%
“…Using r st = a(q 0 = 0)δ q 0 ,0 , Z st (x) = a(q 0 )e −iq 0 x G(q 0 ), with a(q 0 ) and a(q 0 = 0) given respectively by Eqs. (54) and (55), and writing u(x, t) as…”
Section: Stabilitymentioning
confidence: 99%
“…A significant part of previous studies assumes symmetry of natural frequency distributions, and bifurcation is found as the synchronization transition referring to the transition from the nonsynchronized state to partially synchronized states. Interestingly, symmetry breaking brings new types of bifurcations that emerge not from the nonsynchronized state but from partially synchronized states and are followed by a discontinuous jump or oscillation of the order parameter [14]. The new types of bifurcations have been observed by performing numerical simulations, and this paper aims to propose a theoretical explanation of the new types of bifurcations.…”
Section: Introductionmentioning
confidence: 96%